Morphological change of lignocellulosic biomass upon retreatment with deep eutectic solvents (DESS) - Gunny, A.A.N; Arbain, Dachyar; Mohamed Daud, M.Z; Kamaludin, N.H.I; Jamal, Parveen (2013)
Deep Eutectic Solvents (DESs) has emerged as new type of Ionic liquids which exhibit similar characteristic with the conventional ILs but with additional advantages. Unlike conventional ILs, DESs are made from renewable, cheaper and greener components. Besides, the process synthesis is relatively easier. In light o the wide application of the conventional ILs in the pretreatment of lignocelluloses, it is interesting to study the application of DESs for degrading biomass. For this purpose, MCC (microcrystalline cellulose) structure was used as a model cellulose/substrate to study the structural change of the substrate using DESs. This is achieved by using Thermal Gravitational Analysis (TGA) and Xray Diffraction Methods. Results showed a great reduction of crystalline structure of MCC treated with the DESs. In addition, the effect of structural change was also studied using the real biomass pretreated with DESs. The work was carried out using Scanning Electron Microscopy (SEM) as tool to analyze the structural changes in the Rice Husk treated with DESs.